Countryside biogeography of Neotropical reptiles and amphibians. Issue 4 (1st April 2014) - Mendenhall, Chase D.; Frishkoff, Luke O.; Santos-Barrera, Georgina; Pacheco, Jesús; Mesfun, Eyobed; Quijano, Fernando Mendoza; Ehrlich, Paul R.; Ceballos, Gerardo; Daily, Gretchen C.; Pringle, Robert M.
Abstract : The future of biodiversity and ecosystem services depends largely on the capacity of human‐dominated ecosystems to support them, yet this capacity remains largely unknown. Using the framework of countryside biogeography, and working in the Las Cruces system of Coto Brus, Costa Rica, we assessed reptile and amphibian assemblages within four habitats that typify much of the Neotropics: sun coffee plantations (12 sites), pasture (12 sites), remnant forest elements (12 sites), and a larger, contiguous protected forest (3 sites in one forest). Through analysis of 1678 captures of 67 species, we draw four primary conclusions. First, we found that the majority of reptile (60%) and amphibian (70%) species in this study used an array of habitat types, including coffee plantations and actively grazed pastures. Second, we found that coffee plantations and pastures hosted rich, albeit different and less dense, reptile and amphibian biodiversity relative to the 326‐ha Las Cruces Forest Reserve and neighboring forest elements. Third, we found that the small ribbons of "countryside forest elements" weaving through farmland collectively increased the effective size of a 326‐ha local forest reserve 16‐fold for reptiles and 14‐fold for amphibians within our 236‐km 2 study area. Therefore, countryside forest elements, often too small for most remote sensing techniques to identify, are contributing ∼95% of the available habitat for forest‐dependent reptiles and amphibians in our largely human‐dominated study region. Fourth, we found large and pond‐reproducing amphibians to prefer human‐made habitats, whereas small, stream‐reproducing, and directly developing species are more dependent on forest elements. Our investigation demonstrates that tropical farming landscapes can support substantial reptile and amphibian biodiversity. Our approach provides a framework for estimating the conservation value of the complex working landscapes that constitute roughly half of the global land surface, and which are experiencing intensification pressure worldwide.